ROLES OF MALIC ENZYMES OF RHIZOBIUM - zhang, ye (My University, 2013)
C4-dicarboxylic acids appear to be metabolized via the TCA cycle in N2-fixing bacteria (bacteroids) within legume nodules. In Sinorhizobium meliloti bacteroids from alfalfa, NAD+-malic enzyme (DME) is required for symbiotic N2-fixation and this activity is thought to be required for the anaplerotic synthesis of pyruvate. In contrast, in the pea symbiont Rhizobium leguminosarum pyruvate synthesis can occur via either the DME pathway or a pathway catalyzed by phosphoenolpyruvate carboxykinase (PCK), pyruvate kinase (PYK), and pyruvate dehydrogenase. Here we report that dme mutants of Sinorhizobium sp. NGR234 formed root nodules on a broad range of plants and that the level of N2-fixation varied from 90% to 20% of wild type depending on the host plants inoculated. NGR234 bacteroids had significant PCK activity and while single pckA and single dme mutants fixed N2 on Macroptilium atropurpureum and Leucaena leucocephala (albeit at a reduced rate), a pckA dme double mutant had no N2-fixing activity (Fix-). Thus, NGR234 bacteroids appear to synthesize pyruvate from TCA cycle intermediates via DME or PCK pathways. These NGR234 data, together with other reports, suggested that the completely Fix- phenotype of S. meliloti dme mutants may be specific to the alfalfa-S. meliloti symbiosis. We therefore examined the ME-like genes azc3656 and azc0119 from Azorhizobium caulinodans, as azc3656 mutants were previously shown to form Fix- nodules on the tropical legume Sesbania rostrata. We found that purified AZC3656 protein is an NAD (P) +-malic enzyme whose activity is inhibited by acetyl-coenzyme A (acetyl-CoA) and stimulated by succinate and fumarate. Thus, whereas DME is required for symbiotic N2 fixation in A. caulinodans and S. meliloti, in other rhizobia this activity can be bypassed via another pathway(s).
In S. meliloti both malic enzymes DME and TME share similar apparent Kms for substrate and cofactors, but differ in their responses to TCA cycle intermediates, with DME activity inhibited by acetyl-CoA and induced by succinate and fumarate. Previous results in our laboratory indicated that DME is essential for symbiotic N2 fixation, while TME fails to functionally replace DME. One possible reason for it is that a high ratio of NADPH/NADP+ in S. meliloti bacteroids prevents TME from functioning in nodules. We sought to lower the NADPH/NADP+ ratio by overexpressing a soluble pyridine nucleotide transhydrogenase (STH). However, metabolite measurements indicated that overproducing STH failed to lower the ratio of NADPH/NADP+ in S. meliloti.
Previous studies assumed that DME and TME might play different roles in central carbon metabolism. To gain insight of their physiological functions, genome-wide microarray analysis was conducted in S. meliloti single dme and tme mutants grown on glucose or succinate. The most striking changes of gene expression were observed in S. meliloti dme mutants grown on succinate. The functions of upregulated genes suggested that DME might play an important role in regulating TCA cycle intermediates, important for the maintenance of metabolic flux through TCA cycle during C4-dicarboxylate oxidation. However, changes of gene expression found in tme mutants were not significant enough to predict the physiological functions of TME protein in central carbon metabolism.
Keywords: Symbiotic; Host-dependent phenotype; malic enzyme; metabolism; rhizobia; nodule; Biology; Environmental Microbiology and Microbial Ecology; Microbial Physiology; Biology